Efraín Miranda Lujan's "Near Death" from the perspective of poetic discourse analysis (Gestionar: revista de empresa y gobierno, 2021)
The objective was to demonstrate the meaning of death in the poem "Near Death" by Efraín Miranda. The applied method was hermeneutics, based on description and reflection, the contributions of phenomenology, structuralism, and the study of signs were taken into account. The interpretation technique was the discourse analysis in its dimensions: textual, semiotic, enunciative, and pragmatic. In the poem "Near Death" the author's suffering due to illness was evidenced.
Keywords: Near death, sadness, poem, dimensions.